ANALISIS STRATEGI BERSAING RUMAH MAKAN (STUDI PADA RUMAH MAKAN DARISA CAFE CAMPUS) - Riswandi, Akbar (Fakultas Ekonomi Universitas Tadulako, 2016)
The purpose of this study is 1) to find out the strengths and weaknesses of Darisa Cafe Campus Restaurant. 2) to find out the opportunities and threats of Restaurant Darisa Cafe Campus. 3) to find out the competitive strategy of Restaurant Darisa Cafe Campus. This research is a qualitative research with key informants are restaurant owners, restaurant managers and consumers. Data analysis techniques used are SWOT analysis (Strength, Weakness, Opportunities, Threats). Based on the results of the SWOT analysis, the result of the strength factor of Restaurant Darisa Cafe Campus has a score of 1.97 and strength factor of 1.09 so it has a total score of 3.06 while the external strategic factor analysis summary (EFAS). The result of the opportunity factor of Restaurant Darisa Cafe Campus has a score of 2.26 from the results of the SWOT diagram at Darisa Cafe Campus Restaurant is in quadrant 2 (Two ) are ST strategies (strengths and threats)